Three-dimensional computational model of a blood oxygenator reconstructed from micro-CT scans. (September 2017) - D'Onofrio, C.; van Loon, R.; Rolland, S.; Johnston, R.; North, L.; Brown, S.; Phillips, R.; Sienz, J.
Highlights: μ CT scans are a feasible tool to rebuild the real world geometry in 3D. A method to quantitatively and qualitatively assess blood oxygenators. CFD and CT as a tool to review a product as manufactured rather than as designed. Abstract: Cardiopulmonary bypass procedures are one of the most common operations and blood oxygenators are the centre piece for the heart-lung machines. Blood oxygenators have been tested as entire devices but intricate details on the flow field inside the oxygenators remain unknown. In this study, a novel method is presented to analyse the flow field inside oxygenators based on micro Computed Tomography ( μ CT) scans. Two Hollow Fibre Membrane (HFM) oxygenator prototypes were scanned and three-dimensional full scale models that capture the device-specific fibre distributions are set up for computational fluid dynamics analysis. The blood flow through the oxygenator is modelled as a non-Newtonian fluid. The results were compared against the flow solution through an ideal fibre distribution and show the importance of a uniform distribution of fibres and that the oxygenators analysed are not susceptible to flow directionality as mass flow versus area remain the same. However the pressure drop across the oxygenator is dependent on flow rate and direction. By comparing residence time of blood against the time frame to fully saturate blood with oxygen we highlight the potential of this method as design optimisation tool. In conclusion, image-based reconstruction is found to be a feasible route to assess oxygenator performance through flow modelling. It offers the possibility to review a product as manufactured rather than as designed, which is a valuable insight as a precursor to the approval processes. Finally, the flow analysis presented may be extended, at computational cost, to include species transport in further studies.